The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/separations10110556
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Volatile Signatures of Fusarium Bulb Rot in Garlic Using Proton-Transfer-Reaction Time-of-Flight Mass Spectrometry and Solid-Phase Microextraction Gas Chromatography/Mass Spectrometry

Alessandro Infantino,
Cosimo Taiti,
Alessandro Grottoli
et al.

Abstract: Fusarium bulb rot, caused by Fusarium proliferatum, is a worldwide disease of garlic, both in the open field and during storage. Early diagnosis of the disease during storage is difficult due to the morphology of the bulbs and cloves. Volatile organic compounds (VOCs) are secondary metabolites produced by several microorganisms, including phytopathogenic fungi and bacteria. In recent years, the development of several techniques for the detection and characterization of VOCs has prompted their use, among others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…A partial least squares discriminant analysis (PLSDA) linear approach was used to characterize species or fresh/dried peppers according to the VOCs identified with the PTR-ToF-MS technique. PLSDA consists of a PLS regression analysis in which the response variable is categorical (Y-block; replaced by a set of dummy variables describing the species or the fresh/dried samples), expressing the class membership of the statistical units [ 22 , 23 , 24 ]. The general architecture of the non-linear model used is a shallow neural network (SNN) [ 25 ], which consists of a single hidden layer with a given number of neurons (50) with a rectified linear unit (ReLU) activation function and one output layer with a softmax activation function (normalized exponential function) that normalizes the output in a range of values between 0 and 1.…”
Section: Methodsmentioning
confidence: 99%
“…A partial least squares discriminant analysis (PLSDA) linear approach was used to characterize species or fresh/dried peppers according to the VOCs identified with the PTR-ToF-MS technique. PLSDA consists of a PLS regression analysis in which the response variable is categorical (Y-block; replaced by a set of dummy variables describing the species or the fresh/dried samples), expressing the class membership of the statistical units [ 22 , 23 , 24 ]. The general architecture of the non-linear model used is a shallow neural network (SNN) [ 25 ], which consists of a single hidden layer with a given number of neurons (50) with a rectified linear unit (ReLU) activation function and one output layer with a softmax activation function (normalized exponential function) that normalizes the output in a range of values between 0 and 1.…”
Section: Methodsmentioning
confidence: 99%
“…Ethanol, ethyl formate, ethyl acetate, 2-methyl-1-propanol, methyl thioacetate, n-propyl acetate, and 3-methyl-1-butanol were identified as potential biomarkers for Fusarium species in onion. Infantino et al [54] identified nine VOCs that differentiated healthy garlic cloves from cloves infected with F. proliferatum. Additionally, a principal component analysis of different datasets (healthy/artificially inoculated/naturally infected cloves) proved this technique to be a useful tool for the early detection of disease development.…”
Section: Biochemical Detectionmentioning
confidence: 99%